Anak Jalanan dan Rumah Belajar Cinta Damai dalam Perspektif Sosiologi Pembangunan: Anak Jalanan dan Rumah Belajar Cinta Damai dalam Perspektif Sosiologi Pembangunan - A. Jurana Anggriana; Adam Maulana; Nur Wahyunita (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2023)
The problem of street children that occurs in Parepare City is a problem that wants to be solved, so someone is needed to handle this problem. Rumah Belajar Cinta Damai is a community involved in empowering street children. This research aims to determine the role played by Rumah Belajar Cinta Damai in efforts to empower street children and to determine the forms of empowerment programs carried out. The research method used is descriptive qualitative using observation, interviews and documentation. The results of the research show that the role of Rumah Belajar Cinta Damai in efforts to empower street children is to provide a forum for street children to develop their potential through literacy programs, develop street children through moral education, and as a liaison with social networks such as students/alumni as well as IAIN Parepare lecturers, BKP (Form of Learning Activities) from Psychology Student of Makassar State University, Puspaga Parepare (Family Learning Center), and batik artists from Solo, Rahayu Owner Amalia Decoration Yayuk and Partinah Owner Girl Wasta Pura took part in empowering street children. The forms of empowerment carried out by Rumah Belajar Cinta Damai are programs in the fields of education, religion, economics and health.